Analisis Karakteristik Sedimen Di Muara Sungai Indragiri - Dendy Ariandi; Mubarak '; Rifardi ' (Ilmu Perairan (Aquatic Science), 2010)
This research was conducted on August 2008 with purpose has to know the characteristics of sediment at estuary of Indragiri river. The method used in thisresearch was survey method.The research found that there were 2 fractions of sediment I.E. mud and sand withthe type of sediment that were mud, sand, and muddy sand. Mean score for thesediment at the estuary of Indragiri River were between 1.72 to 7.14 Φ anddominated by medium class of silt and coarse silt. The sorting score were between0.58 to 2.10 Φ and dominated by a poorly sorted classification. Skewnes valueindicates the estuary area described that the coarse sediments particles and areas farfrom the mouth of the river showed a trend of fine sediment particles.Keyword: sediment, mud and sand